2009
DOI: 10.2174/1874318809003010022
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Recombinant Corynebacterium pseudotuberculosis Heat-Shock Protein (Hsp)-60 is Able to Induce an Immune Response in Mice, But Fails to Confer Protection Against Infection

Abstract: Corynebacterium pseudotuberculosis is the etiological agent of caseous lymphadenitis (CLA), a chronic small ruminant's disease. C. pseudotuberculosis Hsp60 expressed in E. coli was purified and tested as a vaccine candidate against CLA. Immunization of BALB/c mice with recombinant Hsp60 (rHsp60) induced a significant anti-Hsp60 IgG response, with greater production of IgG1 than of IgG2a. Cell-mediated immune responses induced by immunization were characterized by elevated production of gamma interferon (IFN-) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…Khan et al [25] demonstrated that the onset of death of immunized mice with GroEL was insignificantly delayed and all the mice died by the seventh day post-infection after they were challenged with 105 CFU of S. pneumoniae. As well as, Pinho and his co-worker showed that the rate of survival of the animals immunized with recombinant HSP60 was slightly higher than that of mice injected with PBS; however, all the animals died within two weeks after challenged with 106 CFU of the virulent C. pseudotuberculosis [26]. Therefore, our results can give strong evidence that immunization of animals with GroEL elicited a good humoral response.…”
Section: Discussionsupporting
confidence: 66%
“…Khan et al [25] demonstrated that the onset of death of immunized mice with GroEL was insignificantly delayed and all the mice died by the seventh day post-infection after they were challenged with 105 CFU of S. pneumoniae. As well as, Pinho and his co-worker showed that the rate of survival of the animals immunized with recombinant HSP60 was slightly higher than that of mice injected with PBS; however, all the animals died within two weeks after challenged with 106 CFU of the virulent C. pseudotuberculosis [26]. Therefore, our results can give strong evidence that immunization of animals with GroEL elicited a good humoral response.…”
Section: Discussionsupporting
confidence: 66%
“…Similar results were reported when rPLD and rHsp60 proteins were used in recombinant subunit vaccines against CLA, wherein the survival rate increased, although formulations failed in conferring protection in C. pseudotuberculosis challenge (Fontaine et al, 2006;Pinho et al, 2009). We hypothesized that the use of only rCP01850 is possibly insufficient to provide adequate levels of protection, requiring an evaluation of which important recombinant proteins related to C. pseudotuberculosis pathogenesis should be associated to improve protection.…”
Section: Discussionsupporting
confidence: 61%
“…The DNA vaccine pTARGET/cp09720 induced a significant increase in IFN-γ levels, indicating a Th1 response, the phenotype related to CLA protection (Brum et al, 2017). Also, recombinant subunit vaccines have been tested for CLA immune prophylaxis, since they are considered safe for inducing lower levels of side effects, resulting in variable protection rates depending on the C. pseudotuberculosis antigen selected (Hodgson et al, 1999;Pinho et al, 2009;Silva et al, 2014;Droppa-Almeida et al 2016;Brum et al 2017;Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cell-mediated immune responses induced by immunization were characterized by an elevated production of IFN-γ and IL-10, while IL-4 concentrations were not significantly increased. However, the subcutaneous administration of rHsp60 did not induce effective protection against intraperitoneal infection with C. pseudotuberculosis [93]. Other studies have identified immunodominant antigens by immunoblotting using the secreted/ excreted proteins of C. pseudotuberculosis with immune sera from infected goats and sheep [50,94,95], but these antigens have not yet been investigated in the context of vaccines.…”
Section: Vaccine Models Tested For Clamentioning
confidence: 99%